Youth Satisfaction in Online Shopping: Mapping The Nexus of Influential Factors - ANDIN SALAMAT, AZNI SYAFENA; MOHD KARIM, ANIS-FARAHWAHIDA; AMINUDDIN, ADNAN; AZMI, MUHAMMAD SYAHMIZAN; ISHAK, NUR KHADIJAH; MD DESA, NUR AINI (Information Management and Business Review, 2024)
Online shopping has become a new trend and an integral part of daily life, as it involves the process of direct browsing and purchasing products and services over the Internet using a web browser. Young people constitute the bulk of online shopping customers because purchasing has become simpler, comparatively cheaper, and more comfortable. Today, most goods and services can be purchased online, where multiple options may be offered by different sellers or brand since there are no boundaries to this shopping experience. This study aimed to look into the factors that influence 270 youths to use online shopping platforms, as most young people are highly engaged with technology and digital media. This study was conducted in Sungai Petani, the biggest town in Kedah, Malaysia. The quantitative study method was employed for the data collection phase of this study. All gathered data have been analyzed using the Statistical Package for the Social Sciences (SPSS) software. Regression, reliability, and descriptive analyses were utilized to assess, verify, and explain the findings of this study. The Pearson Correlation has indicated that the variety of selections and time-saving features were significant towards youth satisfaction in online shopping. Meanwhile, two independent variables, i.e., convenience and price fairness showed a considerable relationship. This study has found that the time-saving feature was the dominant factor among four variables that have influenced youth satisfaction in online shopping.